Research methods in criminal justice and criminology - Rennison, Callie Marie (SAGE Publications, 2019)
Why study research methods? -- Setting the stage of your research -- Identifying a topic, a purpose, and a research question -- Conducting a literature review -- Designing your research -- Concepts, conceptualization, operationalization, measurement, variables, and data -- Sampling -- Research using qualitative data -- Survey research -- Experimental research -- Research using secondary data -- Gis and crime mapping -- Evaluation research -- Analysis and findings -- Making your research relevant -- Research methods as a career -- Glossary -- References -- Index